STUDY OF THE EFFECT OF THE COMBINATION OF HALOTHERAPY AND BREATHING GYMNASTICS IN CHILDREN WITH BRONCHIAL ASTHMA - Irina Karaganova; Stefka Mindova (Journal of IMAB, 2024)
Purpose. To date, there is no developed program and in-depth analysis of the complex impact of the effect of the combination of halotherapy and respiratory gymnastics in children with bronchial asthma, and the effect of its application on the disease has not been tracked. For this reason, referring to the successful results of the combined application of physiotherapeutic techniques, natural and reshaped physical factors in the recovery process in bronchial asthma in childhood, the following research goal was set: to implement the combined application of respiratory gymnastics and halotherapy for more effective rehabilitation program and optimal functional recovery in children with bronchial asthma and to track the effect of its impact. Material/Methods. The study was conducted from October 2018 to March 2020 in the city of Razgrad, Bulgaria, in the Resonance after-school training center. Results. The results show that properly conducted respiratory rehabilitation, combining the application of respiratory gymnastics and aerosol therapy, can contribute to the improvement of clinical indicators, reducing the frequency and severity of paroxysmal conditions, improving ventilation indicators, some gas parameters, physical capacity and quality of life. Conclusions. There are objective grounds for asserting that the tested physiotherapy program with an emphasis on respiratory gymnastics and halotherapy has a positive effect on the functional status of children with bronchial asthma and contributes to achieving independence in daily activities and improving their quality of life.